Pengaruh Model Problem-Based Learning (PBL) Terhadap Keterampilan Berpikir Kreatif Dan Hasil Belajar Siswa Pelajaran IPA Kelas VII SMP Negeri 3 Palu - Yulianingtias, Harina Pangestu; Tiwow, Vanny M.A.; Diah, Anang W. M. (Mitra Sains, 2016)
This research aimed to describe influence of problem-based learning (PBL) towards students’ creative thinking skill and learning achievement at Class VII of SMPN 3 Palu. The research implemented quasi-experimental using control group pretest-posttest design. The samples of the research were Class VII F (as experimental group) and Class VII I (as control group). Research data were collected using creative thinking skill test and learning achievement test and were analyzed by t-test and descriptive statistic method. Results of the research showed that there was significant difference (α = 0,05) for (1) creative thinking skill and (2) learning achievement between the both groups. Analysis on normalized gain (<g>) showed that the experimental group outaperformed the control group in the two aspects. It could be concluded that problem-based learning had significant influence on students’ creative thinking skill and learning achievement at Class VII of SMPN 3 Palu.